2017
DOI: 10.4309/jgi.2017.35.3
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for pathological gambling along a continuum of severity: Individual and relational variables

Abstract: This study's aim was to identify characteristics with higher odds of distinguishing a group of pathological gamblers (PG) from (1) a group of gamblers without a gambling problem (NP) and 2) a sub-clinical group (SP). An additional aim was to investigate those characteristics as risk/protective factors along the continuum of problemgambling severity. Sociodemographic (gender, age, marital status, and educational level), individual (psychopathological symptoms) and relational (family functioning, dyadic adjustme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…In the impulsivity, moderate gamblers were higher than non-problem or low risk gamblers. This is consistent with the previous studies [21,22]. Problem gamblers are prone to impulse control disorders [21].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the impulsivity, moderate gamblers were higher than non-problem or low risk gamblers. This is consistent with the previous studies [21,22]. Problem gamblers are prone to impulse control disorders [21].…”
Section: Discussionsupporting
confidence: 93%
“…The prevalence rates of gambling addiction were 20.5% among male students and 8.6% among female students. There are other studies which identified male students are more serious than female students in a gambling problem [19][20][21][22]. Huang et al identified 4.3% of male students and 0.4% of female students as problem or pathological gamblers in the USA [19].…”
Section: Discussionmentioning
confidence: 99%
“…Our selection of risk factors was informed by recent reviews of the literature [4,8,9,10,20,22,23,24], but was necessarily limited to factors that could be measured by self-report.…”
Section: Methodsmentioning
confidence: 99%
“…A large number of demographic factors have been shown to be predictors of adult gambling problems. Poor academic performance [ 61 ] and lower educational attainment [ 59 , 60 , 68 ] are commonly identified risk factors. Male gender is as another key risk factor, with young men being several times more likely to experience problems than many other age-gender categories [ 58 , 60 , 61 , 63 ].…”
Section: Introductionmentioning
confidence: 99%
“…Poor academic performance [ 61 ] and lower educational attainment [ 59 , 60 , 68 ] are commonly identified risk factors. Male gender is as another key risk factor, with young men being several times more likely to experience problems than many other age-gender categories [ 58 , 60 , 61 , 63 ]. Young women, as well as men, are generally more likely to experience problems [ 59 , 62 , 63 ].…”
Section: Introductionmentioning
confidence: 99%